Structural and photophysical characterization of highly luminescent organosilicate xerogel doped with Ir(III) complex - Vilela, Raquel R. C.; Zanoni, Kassio P. S.; de Oliveira, Marcos; de Vicente, Fábio S. [UNESP]; de Camargo, Andrea S. S. (Springer Nature, 2021)
In the search for appropriate host matrices for highly luminescent molecular guest species, an organo-silica monolithic xerogel prepared by the hydrolysis and co-condensation reactions of 3-glycidoxypropyltrimethoxysilane (GPTS) and tetraethylorthosilicate (TEOS) is proposed. Such alkoxides allowed the development of hybrid silica monoliths with a cross-linked three-dimensional structure, in which the silica domains are strictly interconnected with the polymeric network. Highly luminescent monoliths were prepared from the immobilization of a blue-green emissive Ir(III) phosphor in the host matrix, with improved luminescent properties attributed to the greater rigidity of the medium and less diffusion of oxygen within the matrix. The structure of the hybrid material was elucidated by high-resolution solid-state NMR, confirming that the final structure of the developed silica matrix is very similar for both Ir(III)-doped and undoped xerogels. Altogether, the experimental strategy used in this work stands as an advance in the design of photo-functional materials with substantial potential for optical and photonic applications. [Figure not available: see fulltext.].
Keywords: Host-guest optical materials; Hybrid host matrices; Ir(III) complexes; Photophysics; Sol-gel; Solid-state NMR